Publikasi Informasi Pada Pembuatan Konten Instagram @Bukune Di PT Bukune Kreatif Cipta - Savitri, Aisy Andini; Pranata, Rici Tri Harpin; Cholagi, Fahmi Fuad (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik USB YPKP, 2025)
This study analyzes the content management of the @bukune Instagram account using the Circular Model of Some: Share, Optimize, Manage, and Engage. Using a qualitative descriptive method through interviews and observation, the research finds that Bukune applies a structured, collaborative strategy. In the Share stage, content is tailored to audience preferences. Optimization is done by evaluating post performance and adapting to trends. The Manage stage highlights coordination among teams, especially content creators. Engagement is built through replies, interactive features, and a personal tone. Content creators serve as a bridge between creative ideas and technical execution, ensuring relevance and appeal. Overall, Bukune’s Instagram functions not only as an information platform but also as a means to build emotional connection with followers.